THE EFFECT OF FERMENTED PURPLE SWEET POTATO (Ipomoea batatas L) IN THE RATION ON THE ANTIOXIDANT PROFILE AND MEAT CHOLESTEROL OF BALI DUCK - Belawa Yadnya, Tjokorda Gede; Sudana, Ida Bagus; Mahardika, I Gede; Mastika, I M. (E-Journal of Animal Science Udayana University, 2013)
An experiment was carried out to the study the effect of fermented purple sweet potato ( Ipomoea batatas L) in the ration on the profile antioxidant and meat cholesterol of bali duck. A Completely Randomized Design (CRD), consisted seven treatments and four replicates each was used in this experiment. The seven treatments were ration without purple sweet potato (Ipomoea batatas L) (treatment A), ration containing 10, 20, and 30% un fermented purple sweet potato (treatment B, C, and D), ration containing 10, 20, and 30% fermented purple sweet potato (treatment E, F, and G). Each treatment consisted of four replicates with four ducks in each replicates with homogenous age and weight. The variables observed including profile antioxidant, antioxidant capacity, malondialdehida (MDA), and superoxida dismutase (SOD); lipid profile : total clolesterol, high density lipoprotein (HDL), low density lipoprotein (LDL), and triglyceride. Feeds offered were iso nitrogenous and iso calory and were given ad lid The result showed that using fermented purple sweet potato in the ration improved antioxidant profile that was increased of antioxidant capacity such as superoxida dismutase (SOD) were significantly (P<0,05), and malondialdehida (MDA) decreased was sinificantly (P<0,05) than those given control diet.. Ducks meat offered control diet contained total cholesterol and LDL 107,66 mg/100 g and 45,55 mg/100g respectively, When offered diet containing un fermented purple sweet potatoes decreased the content of cholesterol and LDL significantly (P<0.05) compared to control. Result of the experiment suggested that the effect of fermented purple sweet potato (Ipomoea batatas L) in the ration improved the antioxidant profile and consentration of the meat cholesterol of bali duck.
Keywords: purple sweet potato (Ipomoea batatas L), fermented, antioxidant profile, meat cholesterol, and bali duck